Simulation of heat transfer in 2D porous tank in appearance of magnetic nanofluid - Manh, Tran Dinh; Nam, Nguyen Dang; Jacob, Kavikumar; Hajizadeh, Ahmad; Babazadeh, Houman; Mahjoub, Mohammed; Tlili, I.; Li, Z. (Elsevier, 2020)
In current two dimensional nanomaterial convective flow, Lorentz force has been utilized to manage the flow pattern. Nano sized powders with homogeneous behavior were dispersed into H2O within a permeable media. Not only the buoyancy force but also the radiation affects the temperature distribution. In addition, nanoparticles’ shape was involved in correlation of estimating nanomaterial behavior. Result demonstrated that convective flow augments with both Rayleigh and Darcy number and lessen with respect to Hartman number. Augmenting Darcy number wills leads to reduce the effect of Lorentz forces. Nuave augment with thermal radiation Rd and decrease with Hartmann number Ha. Thinner boundary layer is an output of augmenting permeability.